PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN GENERASI Z - Caroline, Meissy; Kaligis, Retor AW (Jurnal Insani, 2021)
The role of employees is very important in a company, so the company must pay attention to the situation of each employee through the existing organizational communication climate. Organizational communication climate can be seen from the communication relationships that exist every day at work. This research was conductedat a well-known interior design company in West Jakarta, namely PT Idefab Cipta. All Generation Z (Gen Z) employees are the main focus of this study, Gen Z employees are those born in the birth year 1995- 2010. This study aims to determine whether there is an influence of organizational communication climate on the performance of Gen Z employees at PT Idefab Cipta. To measure these objectives, researchers used the concept of organizational communication climate, employee performance, and Gen Z. The research was conducted using quantitative methods. The sampling technique used census sample and obtained 49 respondents who were all employees of the Gen Z PT Idefab Cipta. The results showed that there is a significant effect of organizational communication climate on the performance of Gen Z employees. Based on the coefficient of determination, the organizational communication climate has an influence of 55% on the performance of Gen Z employees.This research is expected to be input for companies to be better able to understand what Gen Z needs to produce better performance.